Respostas
respondido por:
4
a) 4(x² + 2) = 8(x +1) ⇒ 4x² + 8 = 8x + 8 ⇒ 4x² + 8 - 8x - 8 = 0
4x² - 8x = 0 Δ = b² - 4ac e o Baskara é x = -b +ou- √/2a lembrando que a = 4, b = -8 e c = 0
b) 3x(x - 1) = 2x ⇒ 3x² - 3x = 2x ⇒ 3x² - 5x = 0 a = 3 b = -5 e c = 0
c) x²/2 - x - 24 = 0 a = 1/2 b = 1 e c = -24
d) 16(x + 1) =7x² ⇒ 16x + 16 = 7x² ⇒ -7x² + 16x + 16 = 0
4x² - 8x = 0 Δ = b² - 4ac e o Baskara é x = -b +ou- √/2a lembrando que a = 4, b = -8 e c = 0
b) 3x(x - 1) = 2x ⇒ 3x² - 3x = 2x ⇒ 3x² - 5x = 0 a = 3 b = -5 e c = 0
c) x²/2 - x - 24 = 0 a = 1/2 b = 1 e c = -24
d) 16(x + 1) =7x² ⇒ 16x + 16 = 7x² ⇒ -7x² + 16x + 16 = 0
Perguntas similares
7 anos atrás
7 anos atrás
7 anos atrás
9 anos atrás
9 anos atrás